2020
DOI: 10.1002/ehf2.12731
|View full text |Cite
|
Sign up to set email alerts
|

Left bundle branch area pacing delivery of cardiac resynchronization therapy and comparison with biventricular pacing

Abstract: Aims This multicentre observational study aimed to prospectively assess the efficacy of left bundle branch area pacing (LBBAP) in heart failure patients with left bundle branch block (LBBB) and compare the 6-month outcomes between LBBAP and biventricular pacing (BVP). Methods and results Consecutive patients with LBBB and left ventricular ejection fraction (LVEF) ≤ 35% were prospectively recruited if they had undergone LBBAP as a primary or rescue strategy from three separate centres from March to December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
209
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(217 citation statements)
references
References 21 publications
4
209
4
Order By: Relevance
“…7,26 Recently, Li et al reported that LBBP-CRT was successful in 81.1% of the heart failure patients with LBBB, and the response rate and super response rate were 88.9% and 44.4%, respectively, which were greater than that of BiV-CRT(66.7% and 16.7%). 27 However, the study wasn't randomizedly designed and the morphological characteristics of LBBB were not strictly defined in their study there may be more patients with"true"LBBB in the LBBP…”
Section: Discussionmentioning
confidence: 99%
“…7,26 Recently, Li et al reported that LBBP-CRT was successful in 81.1% of the heart failure patients with LBBB, and the response rate and super response rate were 88.9% and 44.4%, respectively, which were greater than that of BiV-CRT(66.7% and 16.7%). 27 However, the study wasn't randomizedly designed and the morphological characteristics of LBBB were not strictly defined in their study there may be more patients with"true"LBBB in the LBBP…”
Section: Discussionmentioning
confidence: 99%
“…All studies focused on CRT candidates with LBBB and HF who underwent permanent LBBP implantation, including primary implantation, 10,12,13,15 unsuccessful LV lead placement 12 and failure to achieve acceptable HBP parameters 11,14 . In brief, there are two methods 16 to identify the location for LBBP lead placement in six studies: the single lead method 10,12–15 and the dual lead method 11 . After confirming the initial site for LBBP the lead is then advanced deep into the septum to achieve left conduction system capture (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The study reported significant shortened QRSd (129.09 ± 15.94 ms from native 180.00 ± 15.86 ms), and all 11 patients had their LVEF improvement by at least 5% of baseline value and 7 patients had an increase in LVEF by more than 20% during follow‐up of mean 6.7 months. In order to evaluate the clinical effects of LBBP against BVP, Li et al 12 . compared 27 patients received LBBP alone to 54 patients with BVP by using two to one propensity score matching to minimize bias based on gender, baseline QRSd, LVEF, and LVEDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evident in LV activation time studies where LV activation time is only minimally increased in RBBB but signi cantly increased in LBBB [23]. LOT-CRT advantage narrowing of QRSd in those patients with the baseline surface ECG of atypical LBBB morphology [24]. LOT-CRT offers the advantage to use the LV lead in addition to LBBAP in a potential scenario of progression of conduction disease.…”
Section: Electrophysiological De Nitionmentioning
confidence: 99%